(untitled) (INTERNATIONAL CONFERENCE ON INTERDISCIPLINARY SCIENCE, 2026)
This article examines the theoretical approaches to vocabulary teaching in foreign language education and highlights their role in the development of communicative competence. The study analyzes major linguistic and pedagogical theories related to vocabulary acquisition, including behaviorist, cognitive, communicative, and constructivist approaches. Special attention is paid to the effectiveness of contextual learning, lexical competence formation, and the integration of modern interactive methods in vocabulary instruction. The article also discusses the importance of vocabulary in improving learners’ speaking, reading, listening, and writing skills. The research emphasizes that successful vocabulary teaching requires a combination of theoretical knowledge, practical application, and learner-centered strategies in modern language classrooms